Arcane Magic - Potvin, Sarah; Coker, Catherine (Reference and user services quarterly, 2013)
Scholarship in Science Fiction Studies has expanded greatly in recent decades. As a field of study, it has been extant in one form or another since the 1940s, with the first peer-reviewed journal, Extrapolation, regularly published since 1959. The rise of science fiction as an area befitting academic attention was concurrent with a contemporary interest in recognizing genre literature as worthy of study. Though the birth of science fiction is often stated as the 1818 publication date of Mary Shelley's Frankenstein, it wasn't until the popularity of pulp magazines such as Amazing Stories in the 1920s that the literature was formally identified as a genre with a particular set of characteristics and noteworthy tropes. In its online incarnation, the SFFRD boasts increased functionality. The Web site currently employs a Python interface drawing on a MySQL database. Entries are full-text searchable and browsable by title, author, subject, and imprint. Users may download or email bibliographic records.